2011
DOI: 10.1002/jbmr.514
|View full text |Cite
|
Sign up to set email alerts
|

Higher premenarcheal bone mass in elite gymnasts is maintained into young adulthood after long-term retirement from sport: A 14-year follow-up

Abstract: Sports that impact-load the skeleton during childhood and adolescence increase determinants of bone strength such as bone mineral content and density; however, it is unclear if this benefit is maintained after retirement from the sport. The purpose of this study was to assess whether the previously reported higher bone mass in a group of premenarcheal gymnasts was still apparent 10 years after the cessation of participation and withdrawal of the gymnastics loading stimulus. In 1995, 30 gymnasts 8 to 15 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 51 publications
6
35
0
Order By: Relevance
“…3B). Continuing throwers (0.92 cm 4 , 95% CI, 0.62-1.24 cm 4 , P < 0.001) normalized to controls maintained 50% of the throwingrelated benefit in torsional strength observed in active throwers (1.83 cm 4 . 95% CI, 1.34-2.32 cm 4 , P < 0.001), whereas former throwers maintained 38% of that benefit (0.69 cm 4 ; 95% CI, 0.42-0.96 cm 4 , P < 0.001).…”
Section: Throwing-related Physical Activity Continued During Aging Mamentioning
confidence: 91%
See 2 more Smart Citations
“…3B). Continuing throwers (0.92 cm 4 , 95% CI, 0.62-1.24 cm 4 , P < 0.001) normalized to controls maintained 50% of the throwingrelated benefit in torsional strength observed in active throwers (1.83 cm 4 . 95% CI, 1.34-2.32 cm 4 , P < 0.001), whereas former throwers maintained 38% of that benefit (0.69 cm 4 ; 95% CI, 0.42-0.96 cm 4 , P < 0.001).…”
Section: Throwing-related Physical Activity Continued During Aging Mamentioning
confidence: 91%
“…2 A and E). The persistent benefit of throwing on size contributed to maintenance of the throwing-derived benefit in bone strength, with former throwers in the 50+ y detraining group (0.62 mm 4 ; 95% CI = 0.33-0.91 mm 4 , P < 0.001) still having more than one-third (33.7%) of the benefit in torsional strength observed in active throwers (1.83 mm 4 ; 95% CI = 1.34-2.32 mm 4 , P < 0.001) (Fig. 2I).…”
Section: Throwing-related Physical Activity During Youth Confers a LImentioning
confidence: 98%
See 1 more Smart Citation
“…This was confirmed in our study by the maintenance of aBMD gain in the late pubertal stages compared with the other 2 groups. Another element in favor of higher peak bone mass in gymnasts is the systematically higher bone mass in retired gymnasts compared with controls (16,47,48).…”
Section: Discussionmentioning
confidence: 99%
“…However, while some studies have reported that retired athletes have higher BMD or BMC than age-matched controls [7,8], the results of other studies suggest that the bone mass gained through exercise is gradually lost after retirement from competition or cessation of training [9,10]. In addition, bone strength can increase without changes in bone mass [11].…”
Section: Introductionmentioning
confidence: 90%